Reducing Stigma Toward Individuals With Schizophrenia Using a Brief Video: A Randomized Controlled Trial of Young Adults. (15th August 2020) - Amsalem, Doron; Yang, Lawrence H; Jankowski, Samantha; Lieff, Sarah A; Markowitz, John C; Dixon, Lisa B
Abstract: Objective: Stigma decreases healthcare seeking and treatment adherence and increases the duration of untreated psychosis among people with first-episode psychosis (FEP). This study evaluated the efficacy of a brief video-based intervention in reducing stigma among youth toward individuals with FEP and schizophrenia. We hypothesized that the social-contact-based video intervention group would reduce stigma more than written vignette and control groups, and the vignette more than the control group. Methods: Using Amazon Mechanical Turk, we recruited and assigned 1203 individuals aged 18–30 to either ( a ) video intervention, ( b ) written description of the same content ("vignette"), or ( c ) nonintervention control arm. In the 90-second video intervention, an empowered young woman with schizophrenia described her FEP and the aspects of successful coping with her everyday life difficulties, exposing the viewer to schizophrenia in the context of her personal narrative. Web-based self-report questionnaires assessed stigma domains, including social distance, stereotyping, separateness, social restriction, and perceived recovery. Results: A MANOVA showed a significant between-group effects for all 5 stigma-related subscales ( P < .001). Post hoc pairwise tests showed significant differences between video and vignette vs control for all 5 stigma domains. Video and vignette groups differed significantly on social distance, stereotyping, and social restriction. Secondary analyses revealed gender differences across stigma domains in the video group only, with women reporting lower stigma. Conclusions: A very brief social contact-based video intervention efficaciously reduced stigma toward individuals with FEP. This is the first study to demonstrate such an effect. Further research should examine its long-term sustainability.